Spit for Science: launching a longitudinal study of genetic and environmental influences on substance use and emotional health at a large US university - Dick, Danielle; Nasim, Aashir; Edwards, Alexis C.; Salvatore, Jessica; Cho, Seung B.; Adkins, Amy; Meyers, Jacquelyn; Yan, Jia; Cooke, Megan; Clifford, James; Goyal, Neeru; Halberstadt, Lisa; et al. (Frontiers in Genetics, 2014)
Finding genes involved in complex behavioral outcomes, and understanding the pathways by which they confer risk, is a challenging task, necessitating large samples that are phenotypically well characterized across time. We describe an effort to create a university-wide research project aimed at understanding how genes and environments impact alcohol use and related substance use and mental health outcomes across time in college students. Nearly 70% of the incoming freshman class (N=2715) completed on-line surveys, with 80% of the students from the fall completing spring follow-ups. 98% of eligible participants also gave DNA. The participants closely approximated the university population in terms of gender and racial/ethnic composition. Here we provide initial results on alcohol use outcomes from the first wave of the sample, as well as associated predictor variables. We discuss the potential for this kind of research to advance our understanding of genetic and environment influences on substance use and mental health outcomes.